PENGARUH BERITA POJOK KAMPUNG DI JTV TERHADAP PERUBAHAN TUTUR KATA KELUARGA SUKU JAWA (STUDI KASUS PADA KELUARGA YANG BERLATAR BELAKANG SUKU JAWA DI KELURAHAN NGINDEN JANGKUNGAN SURABAYA) - Rachmanady, Muammal; Hamim, Hamim; Wibowo, Judhi Hari (Universitas 17 Agustus 1945 Surabaya, 2018)
JTV is one of the first local television that carries the local culture, the program'smost inviting attention is Pojok Kampung. Suroboyoan news presentation uses languageraises the pros and cons in eastern Java community. because by some consider thelanguage used is too rough. As for the purpose of this study to analyze the effect of thenews is there any Pojok kampung in JTV to changes in speech tribal family of Java afterviewing pojok kampung, as well as to analyze the impact. Research conducted in thevillages Nginden stilts Javanese ethnic backgrounds with a duration of study 1 June2016-2 July 2016. Mechanical analysis using simple linear regression analysis. From theanalysis and discussion can be concluded that the news shows the pojok kampung inJTV significant and positive impact on the changes in speech-language, The effect showsthat the better the language used in news presentation the better pojok kampung ininfluencing the spoken word in the language. according to the results in the field thatshowed less good words to say on the news shows the pojok kampung in JTV will be ableto give unfavorable influence also on changes in speech-language within the family orcommunityKeywords : pojok kampung, speech, language style